Analisis Identifikasi Hazard Guna Meningkatkan Aspek Keselamatan di Service Road Bandar Udara I Gusti Ngurah Rai - Bali - Novan Muhammad Saofi Arkaan; Ubaedillah Ubaedillah; Rini Sadiatmi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze hazard identification in order to improve operational safety aspects in the service road area of I Gusti Ngurah Rai International Airport, Bali. This area is a vital part of the airside that has a high level of activity and complex safety risks, thus requiring special attention to potential hazards that may arise. The research method used is a qualitative descriptive approach, with data collection techniques through direct observation in the field, in-depth interviews with related personnel, and documentation studies relevant to the airport's safety system and operational procedures. The results of the study indicate that there are still significant potential safety risks in the service road area. Some key findings include haphazard parking practices by Ground Support Equipment (GSE), undisciplined behavior of ground handling personnel, and passenger movement in the operational area without adequate officer supervision. These problems are largely caused by weak supervision from the Apron Movement Control (AMC) unit, as well as the low level of understanding and implementation of safety culture among field workers. Through the process of identifying and assessing risks using the Hazard Identification and Risk Assessment (HIRA) approach, researchers succeeded in mapping the severity of risks and developing appropriate mitigation measures, such as regulating GSE parking procedures, improving safety training, and adding supervisory personnel at vulnerable points. It is hoped that the findings of this study can be a basis for consideration for the management of I Gusti Ngurah Rai International Airport, Bali, in formulating policies and strategies for improving operational safety as a whole, especially in implementing a more effective and sustainable Safety Management Sistem (SMS).